The differential effects of rural health care access on race-specific mortality - Jeralynn Cossman; Wesley James; Julia Kay Wolf (Elsevier, 2017)
We examined the relationship between race-specific rural mortality and the health infrastructure of rural counties in light of America's recent emergence of a rural mortality penalty. Using the Compressed Mortality File from National Center for Health Statistics (2008-2012) and county-level demographic, socioeconomic, and health care indicators from the Area Health Resource File and the US Census, we created a rural public health infrastructure index which encompasses four types of health care access (public health employees, critical access hospital/rural referral centers, rural health clinics, and emergency departments) within counties. We found that each unit increase in the index is associated with a decline in rural Black mortality, but is associated with an increase in rural White mortality. Policymakers could benefit from focusing on the declining rate of mortality improvement in many rural regions, specifically by trying to better understand how decisions concerning public health spending may influence mortality differently for Black and White residents.